Intraoperative imagining in breast cancer surgery - Anna Bigdoń; Maciej Ćwiek; Przemysław Gorczyca; Mateusz Góra; Adrian Hunek; Martyna Kozłowska; Rafał Kreft; Patryk Sydor; Marcel Wartacz; Aleksander Woźniak (Kazimierz Wielki University, 2023)
Breast cancer is the most common cancer in the female population. It is the second leading cause of cancer death in this population. The current technique of nuclear medicine combined with oncological surgery requires the improvement of known imaging methods. In addition to generally available methods, such as MRI, CT, PET or mammography, scientists try to modify the diagnostic process and treatment of the patient in such a way that it is as effective and the least harmful as possible. Breast cancer surgery is experiencing an infamous boom due to the increase in diagnoses, but looking at the positive side, it is also experiencing an amazing development: clinical and technological. Increasingly, surgeons are accompanied by nuclear medicine, which precisely defines the methods of excision of breast tumors with a margin, while giving  a satisfactory cosmetic effect, which is especially important for women. Thanks to the development of these two fields, it is becoming easier to identify specific sentinel lymph nodes (SLNs) that require resection during surgical treatment and to suggest postoperative treatment. The progress of science and medicine has undoubtedly contributed to the development of methods of intraoperative imaging in breast cancer. Today, practically simultaneously in the conditions of the operating room, a multidisciplinary team can determine the area of resection faster and more accurately. Based on the research, it was decided to compare several methods used in today's advanced breast cancer surgery, supported by nuclear medicine.